Private Actors on the Rise? The Role of Non-State Actors in Compliance with International Institutions - Tanja Börzel (Max-Planck-Projektgruppe Recht der Gemeinschaftsgüter, 2000)
(Transnational) private actors have a significant role in `global governance'. But their influence varies significantly, both across time and issues. The major challenge for theorizing about non-state actors in world politics is not only to demonstrate that they matter but explain where, when, and how they matter. This paper takes issue with these challenges by looking at the role of private actors in compliance with international institutions. The first part of the paper clarifies the concept of compliance and the distinction made between public and private actors. The second part reviews prominent approaches to compliance in the International Relations literature. I distinguish them, first, according to the relative weight they attribute to private actors in compliance, and second, according to the causal mechanisms through which compliance is induced granting private actors different ways for influencing compliance. Taking `misfit' as a precondition of non-compliance, I derive 11 hypotheses about state compliance with inconvenient international rules, which specify different causal mechanisms through which state actors, international institutions, and private actors, respectively, impact on compliance. The final part of the paper discusses the EU as a critical case for testing compliance theories.
Keywords: 340